Indicateurs et cartographie dynamique du bruit, un instrument de reconfiguration des politiques publiques ? - Philippe Zittoun (Développement Durable et Territoires)
The indicators of sustainable development are an instrument in full rise in a lot of European cities. How are they built? Who manufacture them? How do they take place to reconfigure the traditional public policies? With the study of an example, the indicator and the map of the "road noise" in Paris, this article proposes to understand the process to transform a new problem into a public policy. The assumption defended here is that indicator appears like a translator and an arranger: A translator because it makes it possible to transform a complex phenomenon into public problem; an arranger since it proposes to attach this problem at victims, a guilty, a legitimate solution to solve it and actors to use it.